Faktor-Faktor yang Mempengaruhi Return Saham pada Perusahaan Sektor Industri Barang Konsumsi yang terdaftar di Bursa Efek Indonesia - Nyayu Khalilah Putri; Nyimas Dewi Murnila Saputri (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study uses the variables Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), and Earnings Per Share to identify the variables that can influence stock returns (EPS). 45 consumer products businesses that were listed on the Indonesia Stock Exchange between 2017 and 2021 were selected as samples in the research utilizing the purposive sampling method. The type of data used is secondary data, which takes the form of publicly available financial records, and multiple regression analysis is used to examine the data. The study's findings show that whereas ROE and DER have a negative and significant impact on stock returns, ROA and EPS have a positive and large impact on stock returns. Additionally, stock returns are impacted by the findings of the research on all variables, including ROA, ROE, DER, and EPS. Keywords: Return On Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER) Earning Per Share (EPS), and Stock Return